Visible-light promoted regioselective amination and alkylation of remote C(sp3)-H bonds - Quanping Guo (Nature Portfolio, 2020)
C-N bond forming is an established strategy to form amines, which are quintessential in chemical synthesis and in nature. Here, the authors report three classes of photoredox reactions, involving C(sp3)-N coupling between N-centered radicals and alkyl radicals and C(sp3)- C(sp3) coupling via C(sp3)-H alkylation.